1981
DOI: 10.1192/bjp.139.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Interviewing Techniques VI. Experimental Study: Eliciting Feelings

Abstract: Four experimental interview styles, designed to differ in the extent of their use of active fact-oriented and active feeling-oriented techniques, were compared in relation to their use in the initial diagnostic interviews with the mothers of children referred to a psychiatric clinic. All four styles proved to be effective in eliciting emotions and feelings, but the findings suggested that each was effective for different reasons. It appeared that emotional expression could be encouraged by the interviewer's re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…This involves restating in the doctor's own words what he or she believes the patient has expressed. Empathic comments are also helpful (Cox et al. 1981; Goldberg et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This involves restating in the doctor's own words what he or she believes the patient has expressed. Empathic comments are also helpful (Cox et al. 1981; Goldberg et al.…”
Section: Resultsmentioning
confidence: 99%
“…1993) by illustrating interest and understanding of the patient's concerns. Questions with a direct psychological focus can also help to elicit information from the patient (Cox et al. 1981; Goldberg et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MJA 71 These open-ended questions can be asked before discussing prognosis, palliative care or end-of-life issues so that the patient's concerns, goals and values can be determined. 72 It can also help create an atmosphere where the patient is treated as a "whole person" (as well as the family) and feels that the health care professional is interested in and sensitive to their problems and feelings.…”
Section: S88mentioning
confidence: 99%
“…The straightest path to increased recognition of adolescent suicidality is simply to ask. In fact, it has been shown that direct questioning, simple empathic support, and attentiveness yield the greatest rates of emotional and behavioral disclosure from adolescents and their parents (93,94). Reducing adolescent access to firearms and assessing for past attempts or future plans of suffocation can appropriately target resources to adolescents with the highest risk of suicide completion.…”
Section: Recognition Of Suicidality In Adolescents In Psychiatric Andmentioning
confidence: 98%